1998
DOI: 10.1017/s0033291798006564
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of needs assessed by staff and by an epidemiologically representative sample of patients with psychosis

Abstract: Staff and patients moderately agree about met needs, but agree less often on unmet needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
131
2
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 12 publications
23
131
2
9
Order By: Relevance
“…This is indicated by the (patient-rated) quality of life being associated only with patient-rated needs and quality of life at baseline, and staff-rated needs at follow-up only being associated with staff-rated needs at baseline. This accords with findings from previous studies that staff and patient ratings of need differ systematically [3, 20, 21, 22, 23]. In summary, the number of needs identified by staff and patients are broadly similar, with a tendency for staff to identify slightly more needs, but the domains of need identified can differ substantially.…”
Section: Discussionsupporting
confidence: 89%
“…This is indicated by the (patient-rated) quality of life being associated only with patient-rated needs and quality of life at baseline, and staff-rated needs at follow-up only being associated with staff-rated needs at baseline. This accords with findings from previous studies that staff and patient ratings of need differ systematically [3, 20, 21, 22, 23]. In summary, the number of needs identified by staff and patients are broadly similar, with a tendency for staff to identify slightly more needs, but the domains of need identified can differ substantially.…”
Section: Discussionsupporting
confidence: 89%
“…Slade et al (1998) found that from a sample of 320 patients with a diagnosis of psychotic disorder, patients, on average, identified both more met and unmet needs than staff (patients identified 0.6 more needs than staff out of a total of 22 needs) using the Camberwell Assessment of Need (CAN; Phelan et al, 1995) (Slade et al, 1996). A similar mismatch was found in a study of 372 staff and users of adult mental health services in Sweden (Arvidsson, 2001).…”
Section: Introductionmentioning
confidence: 64%
“…Scale of Suicide Ideation (SSI) is a self-rating scale with 19 statements of suicidal ideation during the last week on a 3-point level of agreement, ranging from 0 to 2 [28]. Camberwell Assessment of Need (CAN) is a tool for comprehensive assessment of needs of patients with serious psychiatric illnesses [29,30,31]. The CAN is a semi-structured interview and estimates the need for professional services during the last month within 22 identified need areas on a threepoint scale (from 0 = "no need", 1 = "met need", to 2 = " unmet need").…”
Section: Interviews and Assessments At One And 12 Monthsmentioning
confidence: 99%
“…The CAN is a semi-structured interview and estimates the need for professional services during the last month within 22 identified need areas on a threepoint scale (from 0 = "no need", 1 = "met need", to 2 = " unmet need"). The 22 need areas have been clustered into five subdomains covering; basic needs, health aspects, social needs, daily functioning and services according to Slade and co-workers [31]. When the study started we found not other instrument but CAN covering the need of help in every-day-living that we intended to investigate.…”
Section: Interviews and Assessments At One And 12 Monthsmentioning
confidence: 99%